Material and method for reducing contents of heavy metals and nitrogen and phosphorus in bottom mud
The covering materials are prepared by calcified shale, steel slag, activated carbon powder and medium-coarse sand. The physical and chemical phosphorus removal mechanism and the method of microbial fermentation and acid production are used to solve the problem of difficult pollution control of heavy metals and nitrogen and phosphorus in river and lake bottom mud, and achieve the goal of achieving Efficient and low-cost pollution reduction and environmental improvement.
Patent Information
- Application Number
- CN202411699167.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-11
AI Technical Summary
It is difficult to control heavy metals and nitrogen and phosphorus pollution in river and lake bottom mud, the treatment and disposal cost is high and there is a risk of secondary pollution.
The covering materials are prepared by calcareous shale, steel slag, activated carbon powder and medium-coarse sand. Through sintering, a solid skeleton-vacuum structure is formed, and the physicochemical phosphorus removal mechanism and the microbial fermentation and acid production method can be used to reduce heavy metals and nitrogen in the bottom silt. Phosphorus content.
Effectively reduce the heavy metal and nitrogen and phosphorus content in the bottom sludge, improve the ecological environment of the water body, reduce treatment costs, and avoid secondary pollution. The heavy metal removal rate and nitrogen and phosphorus purification capacity are significantly improved.
Smart Images

Figure CN119409392A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a material suitable for reducing the content of heavy metals and nitrogen and phosphorus in sediment and a preparation method thereof, which can reduce the content of heavy metals and nitrogen and phosphorus in sediments of rivers and lakes, improve the ecological environment of water bodies, and belong to the technical field of sediment pollution remediation. Background Art
[0002] Bottom sediments in natural waters are important reservoirs of pollutants, especially in urban rivers. Due to the relatively imperfect pipe network system, a large amount of sewage can easily flow into the river through the rainwater outlet, which will lead to serious pollution of the bottom sediment in the long run. The main pollutants accumulated in the bottom sediments are heavy metals and nitrogen and phosphorus nutrients, which can reach hundreds of times the content in the water body and maintain a certain dynamic balance with the water body. When external pollution is effectively controlled, the deterioration of the water quality environment is mainly caused by the continuous release of pollutants in the bottom sediments into the overlying water. Heavy metals in the bottom sediments not only pollute the water body, but also cause health risks such as cancer to the human body through the food chain. In view of this situation, it is urgent to adopt appropriate remediation technologies to remove and reduce the concentration of heavy metals in the bottom sediments.
[0003] The remediation of contaminated sediment can be divided into in-situ remediation and ex-situ remediation. In-situ remediation refers to the technology of remediating pollution in situ without removing the contaminated sediment from the water body. Ex-situ remediation refers to the use of physical, chemical and biological methods to treat the sediment after dredging to eliminate the harm of pollutants to the water environment. Although the ex-situ remediation is effective, it requires a large amount of work and investment. If the dredged sediment is not further treated or treated improperly, it will cause secondary pollution to the environment. This technology is often used for the treatment and disposal of heavily contaminated sediment. For lightly contaminated sediment, in-situ treatment technology is often used. The main in-situ remediation technologies are: in-situ covering technology, in-situ chemical remediation technology, and in-situ biological remediation technology. In-situ chemical remediation technology is a remediation method that mixes chemical agents with contaminated sediment and fixes or converts heavy metals in the sediment into non-toxic or low-toxic valence states under a series of chemical reactions. In situ bioremediation technology is to directly treat contaminated sediments in situ in the contaminated area, using aquatic plants, enzymes and special microorganisms to enrich or transform heavy metals in the sediments to remove pollution or reduce their toxicity.
[0004] In-situ physical and chemical remediation technologies are becoming increasingly mature. Although physical remediation can significantly reduce heavy metal pollution in a short period of time, some seasonal rivers are shallow and require periodic dredging, so it is not very practical. Chemical remediation has significant effects, but the addition of chemicals can easily cause secondary pollution of the water body.
[0005] Compared with other restoration methods, in situ bioremediation does not require the addition of large amounts of chemical agents into the river channel. Instead, the river channel itself absorbs and enriches heavy metals and nitrogen and phosphorus nutrients in the sediment, and ultimately reduces the content of heavy metals and nitrogen and phosphorus nutrients in the sediment through degradation, achieving restoration effects. This technology is low-cost and has certain ecological effects.
[0006] However, the in-situ bioremediation technology has not yet been popularized and applied, and there is no relevant technical application process. Summary of the invention
[0007] Heavy metal, nitrogen and phosphorus pollution in river and lake sediments is difficult to control, the cost of treatment and disposal is high, and there is secondary pollution. The present invention provides a covering material and a preparation method thereof that is adapted to local conditions, has no secondary pollution, and has good ecological effects and is low-cost for reducing heavy metal and nitrogen and phosphorus pollution in sediments.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] The present invention first provides a material suitable for reducing the content of heavy metals and nitrogen and phosphorus in sediment, comprising the following components by weight:
[0010] 100 parts of calcareous shale, 20-40 parts of steel slag, 6-10 parts of activated carbon powder, and 6-10 parts of medium-coarse sand.
[0011] Furthermore, the mass proportions of the components are: 100 parts of calcareous shale, 30 parts of steel slag, 8 parts of activated carbon powder, and 8 parts of medium-coarse sand.
[0012] The present invention also provides a sintered material suitable for reducing the content of heavy metals and nitrogen and phosphorus in sediment, which is formed by sintering a mixed material, and is characterized in that the mixed material includes the following components by weight:
[0013] 100 parts of calcareous shale, 20-40 parts of steel slag, 6-10 parts of activated carbon powder, 6-10 parts of medium-coarse sand; 2-4 parts of adhesive.
[0014] Furthermore, the mass proportions of the components are: 100 parts of calcareous shale, 30 parts of steel slag, 8 parts of activated carbon powder, 8 parts of medium-coarse sand; and 4 parts of adhesive.
[0015] The present invention also provides a method for preparing a sintered material, comprising:
[0016] The calcareous shale, steel slag and activated carbon are crushed respectively, and the crushed particle size is 2 to 5 mm;
[0017] The crushed steel slag and activated carbon are ground and then air-selected. The particle size of the air-selected material is 70-80μm.
[0018] Pour the divided materials into the container according to the proportion, dry mix and then add water to stir, stir until the moisture content meets the granulation requirements, and then use a mold to press into particles with a diameter of 2 to 5 mm;
[0019] The prepared particles are used for sintering.
[0020] The prepared particles are used for sintering, including:
[0021] Preheating and roasting the prepared particles; the preheating time is 50 to 60 minutes, and the preheating temperature is 220 to 320°C; the roasting time in the roasting section is 10 to 12 minutes, and the roasting temperature is 400 to 600°C;
[0022] After firing, keep warm and cool for 24 hours.
[0023] The present invention also provides a method for reducing the content of heavy metals and nitrogen and phosphorus in sediment, wherein the above-mentioned materials for reducing the content of heavy metals and nitrogen and phosphorus in sediment are mixed and then covered on the sediment or sintered materials are covered on the sediment.
[0024] The material for reducing the heavy metal and nitrogen and phosphorus content in the sediment has a covering thickness of 2cm to 3cm on the sediment.
[0025] The calcareous shale refers to shale containing a large amount of CaCO3, but its content does not exceed 25%. It is widely distributed and is commonly found in the red rock system of the continental phase and transitional phase, and is also found in the marine phase. Its composition and characteristics are mainly formed by clay deposition under pressure and temperature, and are mixed with quartz, feldspar fragments and other chemical substances. It will foam when it encounters dilute hydrochloric acid and can react with dilute hydrochloric acid. Its water absorption characteristics are that the water absorption of calcareous shale increases with time under water pressure and no water pressure conditions, and the water absorption rate decreases with time.
[0026] The steel slag is a byproduct of the steelmaking process, mainly formed by oxidation of impurities such as silicon, manganese, phosphorus, and sulfur in pig iron, and contains a variety of useful components. The steel slag contains 2% to 8% of metallic iron, 40% to 60% of calcium oxide, 3% to 10% of magnesium oxide, and 1% to 8% of manganese oxide.
[0027] The activated carbon powder is mainly composed of carbon and also contains a small amount of oxygen, hydrogen, sulfur, nitrogen and chlorine. It is a black powdery, granular or pelletized amorphous porous carbon with a large surface area and strong adsorption performance, and can adsorb gas, liquid or colloidal solid on its surface. The activated carbon powder is ground into a powdery substance of about 200 mesh.
[0028] The medium-coarse sand has a particle size modulus of 3.0 to 2.3 and an average particle size of 0.35 mm to 0.5 mm. It is mainly composed of glass sand, corundum, bentonite, volcanic rock, etc., and the mud content should not exceed 3%, and it should not contain organic debris such as grass roots and garbage.
[0029] The ultra-high temperature hot melt adhesive is a water-based high molecular inorganic adhesive, the main components of which are potassium, sodium, magnesium, and aluminum salts of phosphoric acid and silicate, oxides of aluminum, potassium, sodium, magnesium, and iron, as well as inorganic fibers and nano-minerals. It has good insulation, acid and alkali resistance, compression resistance, and peeling resistance, and stable physical and chemical properties. It is resistant to high temperatures and heat, has strong thermal insulation, and can withstand high temperatures up to 1350°C. The fire-resistant combustion performance reaches A1 level, and the smoke toxicity reaches the safety level.
[0030] Advantages of the invention:
[0031] (1) With calcareous shale and steel slag as the main raw materials, the denitrification efficiency of sludge was significantly improved according to the chemical composition characteristics and firing requirements. In addition, the physicochemical phosphorus removal mechanism of calcareous shale and steel slag can also significantly improve the phosphorus removal efficiency.
[0032] (2) Selecting activated carbon powder and medium-coarse sand as auxiliary raw materials helps the filler to form a solid skeleton-void structure. The skeleton-void structure gives it a larger specific surface area and a richer pore structure, which can significantly increase the content of microorganisms such as Aspergillus niger. Using Aspergillus niger to ferment and produce acid under specific conditions to leach heavy metals in river and lake sediments can effectively remove heavy metals in the sediments.
[0033] (3) This covering material not only blocks the pollution of water quality by sludge, but also effectively reduces the content of heavy metals and nitrogen and phosphorus nutrients in the sediment in situ, and can also reduce the thickness of the sediment, improve the characteristics of the sediment, and truly achieve harmless treatment of the sediment.
[0034] (4) Compared with traditional treatment materials on the market, such as expanded clay, volcanic rock, etc., it has increased the ability to remove heavy metals, and the nitrogen and phosphorus purification capacity has also been greatly improved, with a lower price for the same volume. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0036] Embodiment 1:
[0037] Bottom sediments in natural waters are important reservoirs of pollutants, especially in urban rivers. Take the Fengjin River in Suzhou as an example. Due to the relatively imperfect pipe network system on both sides of the river, there is mixed flow of rainwater and sewage. After long-term accumulation, the content of heavy metals and nitrogen and phosphorus in the bottom sediment is high.
[0038] After on-site investigation, an area of about 1,000 square meters of Fengjin River was selected as a demonstration area for sediment treatment.
[0039] First, three sampling monitoring points were evenly set up in the demonstration area. After sampling and testing, the specific values of heavy metal content and nitrogen and phosphorus content in the bottom mud of the demonstration area are as follows:
[0040]
[0041] The demonstration area does not require precipitation, and uses about 30m 3 The granular covering material of the present invention (the third stage in the test process below - pilot test two - group ① test material) is evenly spread into the water and sinks to the bottom of the water to form a covering layer of 2 cm to 3 cm thick.
[0042] On the 5th, 10th and 15th days, sediment sampling was carried out at the three monitoring points. The specific values of heavy metal content and nitrogen and phosphorus content in the sediment are shown in the following table.
[0043]
[0044] On the 5th day after the novel granular covering material of the present invention is used, the removal rate of heavy metals in the bottom mud at the D1 point, such as copper (Cu), zinc (Zn), mercury (Hg), arsenic (As), nickel (Ni), lead (Pb), cadmium (Cd) and chromium (Cr), is 22% to 59%; the removal rate of heavy metals in the bottom mud at the D2 point, such as copper (Cu), zinc (Zn), mercury (Hg), arsenic (As), nickel (Ni), lead (Pb), cadmium (Cd) and chromium (Cr), is 26% to 50%; the removal rate of heavy metals in the bottom mud at the D3 point, such as copper (Cu), zinc (Zn), mercury (Hg), arsenic (As), nickel (Ni), lead (Pb), cadmium (Cd) and chromium (Cr), is 24% to 46%.
[0045] On the fifth day after the novel granular covering material of the present invention was used, the removal rate of ammonia nitrogen in the bottom mud at point D1 was 47%, the removal rate of TN was 29%, and the removal rate of total phosphorus was 59%; the removal rate of ammonia nitrogen in the bottom mud at point D2 was 37%, the removal rate of TN was 24%, and the removal rate of total phosphorus was 54%; the removal rate of ammonia nitrogen in the bottom mud at point D3 was 47%, the removal rate of TN was 30%, and the removal rate of total phosphorus was 57%.
[0046]
[0047] On the 10th day after the new granular covering material of the present invention is used for covering, the removal rate of heavy metals in the bottom mud at the D1 point is 67%-89%; the removal rate of heavy metals in the bottom mud at the D2 point is 65%-89%; the removal rate of heavy metals in the bottom mud at the D3 point is 68%-92%.
[0048] On the 10th day after the new granular covering material of the present invention was used to cover the bottom mud at point D1, the removal rate of ammonia nitrogen was 81%, the removal rate of TN was 55%, and the removal rate of total phosphorus was 89%. The removal rate of ammonia nitrogen in the bottom mud at point D2 was 83%, the removal rate of TN was 54%, and the removal rate of total phosphorus was 87%. The removal rate of ammonia nitrogen in the bottom mud at point D3 was 81%, the removal rate of TN was 57%, and the removal rate of total phosphorus was 84%.
[0049]
[0050] On the 15th day after the new granular covering material of the present invention is used for covering, the removal rate of heavy metals in the bottom mud at the D1 point is 68%-90%, the removal rate of heavy metals in the bottom mud at the D2 point is 68%-90%, and the removal rate of heavy metals in the bottom mud at the D3 point is 68%-92%.
[0051] On the 15th day after the new granular covering material of the present invention was used to cover the bottom mud at point D1, the removal rate of ammonia nitrogen was 84%, the removal rate of TN was 57%, and the removal rate of total phosphorus was 93%. The removal rate of ammonia nitrogen in the bottom mud at point D2 was 84%, the removal rate of TN was 59%, and the removal rate of total phosphorus was 90%. The removal rate of ammonia nitrogen in the bottom mud at point D3 was 87%, the removal rate of TN was 57%, and the removal rate of total phosphorus was 87%.
[0052] In summary
[0053] By comparing the heavy metal monitoring data on the 5th day and the 10th day, the removal rates of copper (Cu), zinc (Zn), mercury (Hg), arsenic (As), nickel (Ni), lead (Pb), cadmium (Cd), and chromium (Cr) among the heavy metals gradually increased and grew rapidly; comparing the data on the 10th day and the 15th day, the heavy metal removal rate was relatively stable. Finally, the detection data on the 15th day was taken as the governance result of the demonstration area. The removal rates of copper (Cu), zinc (Zn), mercury (Hg), arsenic (As), nickel (Ni), lead (Pb), cadmium (Cd), and chromium (Cr) among the heavy metals were 68% to 92%.
[0054] By comparing the nitrogen and phosphorus monitoring data on the 5th day and the 10th day, the removal rates of ammonia nitrogen, total nitrogen and total phosphorus gradually increased and grew rapidly, especially the removal effects of ammonia nitrogen and total phosphorus were extremely high; comparing the data on the 10th day and the 15th day, the removal rates of ammonia nitrogen, total nitrogen and total phosphorus were relatively stable, and finally the average values of the test data D1, D2 and D3 on the 15th day were taken as the management results of the demonstration area. The removal rates of ammonia nitrogen were 85%, TN was 58%, and total phosphorus was 90%.
[0055] Taking this as an example, for similar water bodies with high heavy metal and nitrogen and phosphorus contents in the sediment, evenly laying a 2 cm to 3 cm thick covering layer of the covering material of the present invention can effectively reduce the heavy metal and nitrogen and phosphorus contents in the sediment in about 15 days, and the treatment effect is obvious.
[0056] The goal of this invention is to use a combination of new materials to more significantly reduce the heavy metal and nitrogen and phosphorus content in the sediment. In the first stage of the production process and data verification, it was found that the use of calcareous shale as the main material significantly improved the denitrification efficiency of the sediment, but the removal efficiency of phosphorus and heavy metals was poor. The second stage focuses on screening the main material suitable for calcareous shale. Through multiple sets of data experiments, it is shown that with the addition of steel slag, the physical and chemical phosphorus removal mechanism of calcareous shale and steel slag can significantly improve the phosphorus removal efficiency without reducing the denitrification efficiency of the sediment. The third stage is mainly to improve the reduction of heavy metals in the sediment by the material. Through multiple sets of data experiments, it is shown that with the addition of activated carbon and medium-coarse sand, activated carbon can better adsorb and aggregate heavy metal ions in the sediment, and medium-coarse sand provides a solid skeleton-void structure for the material. The skeleton-void structure can significantly increase the content of microorganisms such as Aspergillus niger. Using Aspergillus niger to ferment and produce acid to leach heavy metals in river sediment under specific conditions can effectively remove heavy metals in the sediment.
[0057] The main test process is as follows
[0058] Phase I Trial:
[0059] Test materials: 1500g of polluted riverbed mud (10% water: 90% mud), 100g of calcareous shale.
[0060] Test method: crush the calcareous shale into particles with a size of 2 to 5 mm, evenly spread them on the surface of the bottom mud to form a covering layer of 2 to 3 cm thick, and place it outdoors to stand.
[0061] Sampling was taken on the 3rd, 6th, 9th and 12th days to test the heavy metal and nitrogen and phosphorus contents. The specific values are shown in the following table.
[0062]
[0063] During the first phase of the test and data testing, it was found that the use of crushed calcareous shale particles can significantly improve the nitrogen removal efficiency of sediment, but phosphorus and heavy metals are almost impossible to remove.
[0064] Phase II Trial:
[0065] Test materials: six parts of polluted riverbed mud (1500g each, 10% water: 90% mud), six parts of calcareous shale (100g each), and six parts of steel slag (100g, 50g, 40g, 30g, 20g, and 10g).
[0066] Test method: crush the calcareous shale and steel slag into particles with a particle size of 2-5 mm, and divide them into six combinations: ① one part of bottom mud 1500g + one part of calcareous shale 100g + one part of steel slag 100g; ② one part of bottom mud 1500g + one part of calcareous shale 100g + one part of steel slag 50g; ③ one part of bottom mud 1500g + one part of calcareous shale 100g + one part of steel slag 40g; ④ one part of bottom mud 1500g + one part of calcareous shale 100g + one part of steel slag 30g; ⑤ one part of bottom mud 1500g + one part of calcareous shale 100g + one part of steel slag 20g; ③ six parts of bottom mud 1500g + one part of calcareous shale 100g + one part of steel slag 10g. Mix them evenly and spread them on the surface of the bottom mud to form a 2cm-3cm thick covering layer, and place them outdoors for static.
[0067] Sampling was taken on the 3rd, 6th, 9th and 12th days to test the heavy metal and nitrogen and phosphorus contents. The specific values are shown in the following table.
[0068]
[0069]
[0070]
[0071]
[0072] During the second phase of the test process and data detection and collation, it was found that the use of crushed particles composed of calcareous shale and steel slag can significantly improve the phosphorus removal efficiency by utilizing the physicochemical phosphorus removal mechanism of the joint reaction of part of the calcareous shale and steel slag without reducing the denitrification efficiency of the calcareous shale on the sediment (the results of the second phase ③④⑤ groups of tests, the removal rates of ammonia nitrogen, total nitrogen and total phosphorus were basically above 75% on the 12th day), and in the 3:1 ratio of calcareous shale and steel slag (the results of the second phase ④ group of tests), the removal rates of ammonia nitrogen, total nitrogen and total phosphorus were the highest from the 9th to the 12th day, and the denitrification and phosphorus removal effects were the best.
[0073] Phase III trials:
[0074] Pilot test 1
[0075] Test materials: three parts of contaminated river bottom mud (1500g each, 10% water: 90% mud), three parts of calcareous shale (100g each), three parts of steel slag (30g each), three parts of activated carbon (4g, 6g, 8g, 10g, 16g), and three parts of medium-coarse sand (4g, 6g, 8g, 10g, 16g).
[0076] Test method: crush the calcareous shale, steel slag and activated carbon into particles with a particle size of 2-5mm, and divide them into 5 combinations according to ① one part of sediment 1500g + one part of calcareous shale 100g + one part of steel slag 30g + one part of activated carbon 4g + one part of medium-coarse sand 4g; ② one part of sediment 1500g + one part of calcareous shale 100g + one part of steel slag 30g + one part of activated carbon 6g + one part of medium-coarse sand 6g; ③ one part of sediment 1500g + one part of calcareous shale 100g + one part of steel slag 30g + one part of activated carbon 8g + one part of medium-coarse sand 8g; ④ one part of sediment 1500g + one part of calcareous shale 100g + one part of steel slag 30g + one part of activated carbon 10g + one part of medium-coarse sand 10g; ⑤ one part of sediment 1500g + one part of calcareous shale 100g + one part of steel slag 30g + one part of activated carbon 16g + one part of medium-coarse sand 16g. Mix them evenly and spread them on the surface of the bottom mud to form a covering layer of 2cm to 3cm thick, and place it outdoors to stand.
[0077] Sampling was taken on the 3rd, 6th, 9th and 12th days to test the heavy metal and nitrogen and phosphorus contents. The specific values are shown in the following table.
[0078]
[0079]
[0080]
[0081]
[0082] In the process and data collection of the third phase pilot test, it was found that the activated carbon can better adsorb and aggregate heavy metal ions in the sediment by using crushed particles of calcareous shale, steel slag, activated carbon and medium-coarse sand. In particular, the heavy metal removal rate was the highest in the mix ratio of activated carbon accounting for 5% (±1%) and medium-coarse sand accounting for 5% (±1%) (the results of the third phase group ③ test).
[0083] Pilot test 2
[0084] Test materials: three parts of polluted riverbed mud (1500g each, 10% water: 90% mud), three parts of calcareous shale (100g each), three parts of steel slag (30g each), three parts of activated carbon (8g), three parts of medium-coarse sand (8g), and three parts of ultra-high temperature hot melt adhesive (4g, 8g, 12g); the ultra-high temperature hot melt adhesive used in this test is the product of Zhuzhou Shilin Polymer Co., Ltd., model XY808; ultra-high temperature hot melt adhesives of other models from other manufacturers can also be used.
[0085] Test method:
[0086] 1. Crush the calcareous shale, steel slag and activated carbon into particles with a particle size of 2 to 5 mm, and divide them into 3 combinations according to ① one part of sludge 1500g + one part of calcareous shale 100g + one part of steel slag 30g + one part of activated carbon 8g + one part of medium-coarse sand 8g + one part of ultra-high temperature hot melt adhesive 4g; ② according to ① one part of sludge 1500g + one part of calcareous shale 100g + one part of steel slag 30g + one part of activated carbon 8g + one part of medium-coarse sand 8g + one part of ultra-high temperature hot melt adhesive 8g; ③ according to ① one part of sludge 1500g + one part of calcareous shale 100g + one part of steel slag 30g + one part of activated carbon 8g + one part of medium-coarse sand 8g + one part of ultra-high temperature hot melt adhesive 12g;
[0087] 2. Crush the calcareous shale, steel slag and activated carbon respectively, with the particle size of 2-5 mm;
[0088] 3. Grind the crushed steel slag and activated carbon, and then air-select them. The particle size of the air-selected materials is 70-80 μm;
[0089] 4. Pour the materials into the container according to the proportion, dry mix and then add water to stir. Stir until the moisture content meets the granulation requirements and then use a mold to press into particles with a diameter of 2 to 5 mm;
[0090] 5. Preheat and roast the prepared particles. The preheating time is 50 to 60 minutes at a preheating temperature of 220 to 320°C. The roasting time in the roasting section is 10 to 12 minutes at a roasting temperature of 400 to 600°C. After firing, keep warm and cool for 24 hours.
[0091] 6. Sprinkle evenly on the surface of the bottom mud to form a covering layer of 2cm to 3cm thick, and place it outdoors to stand.
[0092] According to the first, second and third stage tests, the removal rate of the covering material generally tends to be stable after 9-10 days. Therefore, this pilot test directly took samples on the 12th day to test the heavy metal and nitrogen and phosphorus content as the removal rate data. The specific values are shown in the following table.
[0093]
[0094]
[0095] Through the process observation and data comparison of the third phase pilot test one and pilot test two, it was found that adding ultra-high temperature hot melt adhesive to the combination of calcareous shale, steel slag, activated carbon, and medium-coarse sand for high-temperature roasting formed a solid skeleton-void structure inside the roasted solid particles. The skeleton-void structure can significantly increase the content of microorganisms such as Aspergillus niger, and use Aspergillus niger to ferment and produce acid under specific conditions to leach heavy metals in riverbed mud. In the unfired state of pilot test one, the heavy metal removal rate was greatly improved compared to relying solely on the single heavy metal adsorption capacity of activated carbon.
[0096] In the data detection and collation of the third phase pilot test II, it was found that as the proportion of ultra-high temperature hot melt adhesive increased, the removal rate of heavy metals and nitrogen and phosphorus decreased. Therefore, the optimal proportion of ultra-high temperature hot melt adhesive should be 3% (±1%).
[0097] In summary
[0098] Due to the numerous experimental processes, the present invention only lists the main experimental processes to illustrate how to obtain the optimal ratio of the present invention step by step. Through a large number of small-scale and pilot tests in three stages, it was found that a covering material suitable for reducing the content of heavy metals and nitrogen and phosphorus in sediments and a preparation method thereof, the main raw materials are calcareous shale and steel slag, and the auxiliary materials are activated carbon powder and medium-coarse sand. The weight ratio of each component in the raw materials is preferably: 100 parts of calcareous shale, 20-40 parts of steel slag, 6-10 parts of activated carbon powder, 6-10 parts of medium-coarse sand; 2-4 parts of adhesive.
[0099] The calcareous shale refers to shale containing a large amount of CaCO3, but its content does not exceed 25%. It is widely distributed and is commonly found in the red rock system of the continental phase and transitional phase, and is also found in the marine phase. Its composition and characteristics are mainly formed by clay deposition under pressure and temperature, and are mixed with quartz, feldspar fragments and other chemical substances. It will foam when it encounters dilute hydrochloric acid and can react with dilute hydrochloric acid. Its water absorption characteristics are that the water absorption of calcareous shale increases with time under water pressure and no water pressure conditions, and the water absorption rate decreases with time.
[0100] The steel slag is a byproduct of the steelmaking process, mainly formed by oxidation of impurities such as silicon, manganese, phosphorus, and sulfur in pig iron, and contains a variety of useful components. The steel slag contains 2% to 8% of metallic iron, 40% to 60% of calcium oxide, 3% to 10% of magnesium oxide, and 1% to 8% of manganese oxide.
[0101] The activated carbon powder is mainly composed of carbon and also contains a small amount of oxygen, hydrogen, sulfur, nitrogen and chlorine. It is a black powdery, granular or pelletized amorphous porous carbon with a large surface area and strong adsorption performance, and can adsorb gas, liquid or colloidal solid on its surface. The activated carbon powder is ground into a powdery substance of about 200 mesh.
[0102] The medium-coarse sand has a particle size modulus of 3.0 to 2.3 and an average particle size of 0.35 mm to 0.5 mm. It is mainly composed of glass sand, corundum, bentonite, volcanic rock, etc., and the mud content should not exceed 3%, and it should not contain organic debris such as grass roots and garbage.
[0103] The ultra-high temperature hot melt adhesive is a water-based high molecular inorganic adhesive, the main components of which are potassium, sodium, magnesium, and aluminum salts of phosphoric acid and silicate, oxides of aluminum, potassium, sodium, magnesium, and iron, as well as inorganic fibers and nano-minerals. It has good insulation, acid and alkali resistance, compression resistance, and peeling resistance, and stable physical and chemical properties. It is resistant to high temperatures and heat, has strong thermal insulation, and can withstand high temperatures up to 1350°C. The fire-resistant combustion performance reaches A1 level, and the smoke toxicity reaches the safety level.
[0104] This scheme also provides a production process of a covering material suitable for reducing the content of heavy metals and nitrogen and phosphorus in sediment and a preparation method thereof, including:
[0105] 1. Store calcareous shale, steel slag, activated carbon and medium-coarse sand in the batching bin according to the corresponding proportions for standby use;
[0106] 2. Put the calcareous shale, steel slag and activated carbon into the crusher for crushing respectively, the crushed particle size is 2-5mm, and after crushing, they are input into the buffer bin by bucket elevator;
[0107] 3. Put the crushed steel slag and activated carbon into the resonance mill for grinding. After grinding, they are sent to the air separation classifier for air separation. The particle size of the air-separated materials is 70-80μm. After air separation, they are sent to their respective powder bins for storage and standby use.
[0108] 4. Introduce the divided materials into the fast vertical axis star mixer in proportion, dry mix and then add water to stir. The materials in the strong mixer are directly put into the granulation process after being stirred to meet the granulation moisture content requirements; the materials in the fast vertical axis star mixer are discharged after being stirred to meet the granulation moisture content requirements, and then the extrusion granulator on the process line is used to complete the granulation;
[0109] 5. The powerful mixer makes the material into spherical particles, and the extrusion granulator makes the material into columnar particles;
[0110] 6. The prepared particles are transported to the rotary kiln through a high-angle belt conveyor for preheating and roasting. The preheating time is 50-60 minutes, the preheating temperature is 220-320°C, the roasting time in the roasting section is 10-12 minutes, the roasting temperature is 400-600°C, and after firing, they enter the cooling kiln for insulation and cooling, and finally put into storage for shipment.
Claims
1. A material for reducing the content of heavy metals and nitrogen and phosphorus in sediment, characterized in that: It includes the following components by mass: 100 parts of calcareous shale, 20-40 parts of steel slag, 6-10 parts of activated carbon powder, and 6-10 parts of medium-coarse sand.
2. The material for reducing the content of heavy metals and nitrogen and phosphorus in sediment according to claim 1, characterized in that: 100 parts of calcareous shale, 30 parts of steel slag, 8 parts of activated carbon powder, and 8 parts of medium-coarse sand.
3. The sintered material for reducing the content of heavy metals and nitrogen and phosphorus in the sediment is sintered by mixed materials and is characterized by: The mixed material includes the following components by weight: 100 parts of calcareous shale, 20-40 parts of steel slag, 6-10 parts of activated carbon powder, 6-10 parts of medium-coarse sand; 2-4 parts of adhesive.
4. The sintered material for reducing the content of heavy metals and nitrogen and phosphorus in sediment according to claim 3, characterized in that: 100 parts of calcareous shale, 30 parts of steel slag, 8 parts of activated carbon powder, 8 parts of medium-coarse sand; 4 parts of adhesive.
5. The method for preparing a sintered material for reducing the content of heavy metals and nitrogen and phosphorus in sediment according to claim 3, characterized in that: include: The calcareous shale, steel slag and activated carbon are crushed respectively, and the crushed particle size is 2 to 5 mm; The crushed steel slag and activated carbon are ground and then air-selected. The particle size of the air-selected material is 70-80μm. Pour the divided materials into the container according to the proportion, dry mix and then add water to stir, stir until the moisture content meets the granulation requirements, and then use a mold to press into particles with a diameter of 2 to 5 mm; The prepared particles are used for sintering.
6. The method for preparing a sintered material for reducing the content of heavy metals and nitrogen and phosphorus in sediment according to claim 5, characterized in that: The prepared particles are used for sintering, including: Preheating and roasting the prepared particles; the preheating time is 50 to 60 minutes, and the preheating temperature is 220 to 320°C; the roasting time in the roasting section is 10 to 12 minutes, and the roasting temperature is 400 to 600°C; After firing, keep warm and cool for 24 hours.
7. A method for reducing the content of heavy metals and nitrogen and phosphorus in sediment, characterized in that: The material for reducing the heavy metal and nitrogen and phosphorus contents in the sediment according to claim 1 or 2 is mixed and then covered on the sediment.
8. The method for reducing the content of heavy metals and nitrogen and phosphorus in sediment according to claim 7, characterized in that: The thickness of the material used to reduce the heavy metal and nitrogen and phosphorus content in the sediment is 2cm~3cm.
9. A method for reducing the content of heavy metals and nitrogen and phosphorus in sediment, characterized in that: The material for reducing the heavy metal and nitrogen and phosphorus content in the sediment according to claim 3 or 4 is mixed and covered on the sediment.
10. The method for reducing the content of heavy metals and nitrogen and phosphorus in sediment according to claim 9, characterized in that: The thickness of the material used to reduce the heavy metal and nitrogen and phosphorus content in the sediment is 2cm~3cm.
Citation Information
Patent Citations
River sediment ecological treatment method
CN109133519A
Preparation method and application of bottom mud heavy metal pollution repairing agent
CN111285574A
River and lake bottom mud covering material as well as preparation method and application thereof
CN114505063A
Preparation method and application of biochar-steel slag composite adsorption material
CN114669268A
Cited By
River sediment in-situ weight removal and phosphorus control material and preparation method thereof
CN120887620A
River channel sediment in-situ heavy metal removal and phosphorus control material and preparation method thereof
CN120887620B